Anti‐CGRP monoclonal antibodies: breakthrough in migraine therapeutics. Issue 3 (13th August 2019) - Krishnaswamy, Ratna; Malik, Bilal Haider; Khan, Safeera; Gupta, Deepti; Islam, Muhammad; Mandal, Shrawan Kumar; Rutkofsky, Ian H
Abstract : Migraine is considered as one of the most debilitating neurological disorders but the success of the anti‐calcitonin gene‐related peptide (CGRP) therapies marks a new era in the treatment of migraine and has paved way for further research into the exact pathophysiology of migraine. Here, the authors discuss their literature review on the anti‐CGRP therapies to examine the pathophysiology of migraine, with a focus on the possible role of CGRP and the safety and efficacy of monoclonal antibodies targeting it.